2013
DOI: 10.1378/chest.12-1604
|View full text |Cite
|
Sign up to set email alerts
|

An Opportunistic Infection Associated With Ruxolitinib, a Novel Janus Kinase 1,2 Inhibitor

Abstract: We report a case of Cryptococcus neoformans pneumonia in a patient taking ruxolitinib, a janus kinase 1,2 inhibitor approved for the treatment of myelofibrosis. We hypothesize that ruxolitinib contributed to this infection through its effects on cell-mediated immunity. Clinicians should be aware of the potential for intracellular or opportunistic infections associated with this novel drug class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 6 publications
2
71
0
3
Order By: Relevance
“…Even though recent clinical trials have not shown markedly increased infection rates, viral reactivation (eg, herpes zoster), urinary tract, and opportunistic infections may be more frequently observed. 33 Thus, potential effects of the drug on infectious prevalence in patients during longterm JAK-inhibitor therapy have to be closely monitored in the future. This assumption is further supported by our second in vivo model, showing that clearance of a hepatic adenoviral infection is delayed by systemic ruxolitinib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Even though recent clinical trials have not shown markedly increased infection rates, viral reactivation (eg, herpes zoster), urinary tract, and opportunistic infections may be more frequently observed. 33 Thus, potential effects of the drug on infectious prevalence in patients during longterm JAK-inhibitor therapy have to be closely monitored in the future. This assumption is further supported by our second in vivo model, showing that clearance of a hepatic adenoviral infection is delayed by systemic ruxolitinib therapy.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Next-generation sequencing can be a powerful tool to identify novel genetic etiologies in patients with unclassified IBMFS, especially in the setting of consanguinity where the causal mutation usually resides within the easily tractable autozygome. 3,4 This phenomenon narrows the candidacy of the large number of variants that are generated by next-generation sequencing, which makes it possible to identify the causal mutation even in simplex cases. 5,6 Thus, the study of unclassified IBMFSs in Saudi Arabia where the consanguinity rate is high represents an opportunity to identify novel disease genes, and these may similarly contribute to the causation of IBMFSs in outbred populations.…”
Section: And Cd8mentioning
confidence: 99%
“…48,49 The DC impairments might result in increased infection rates, while the NK cell dysfunction may impair the GVL effect. 50 Conversely, JAK inhibitors appear to reduce acute GVHD in murine models by increasing T-regulatory cells, which has led to the successful treatment of six patients with ruxolitinib for steroidrefractory acute GVHD. 51 Another JAK inhibitor, tofacitinib, a selective JAK3 inhibitor, has been found to reverse CD8 + T-cellmediated mucocutaneous GVHD-like disease in a murine model.…”
Section: Impact Of Targeting the Jak/signal Transducers And Activatormentioning
confidence: 99%